2017
DOI: 10.1007/978-3-319-67633-3_12
|View full text |Cite
|
Sign up to set email alerts
|

Learners’ Assessment and Evaluation in Serious Games: Approaches and Techniques Review

Abstract: Abstract. Recently, there has been growing interest in the use of Serious Games (SG), as they provide a more powerful means of knowledge transfer in almost every application domain especially in the crisis management field. With this increasing adoption of SG, designing novel techniques for learners' assessment and evaluation has become of paramount importance to improve learning results and thus to maintain players' motivation. This paper focuses on the learners' assessment and evaluation in SG. After definin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
3
0
2
Order By: Relevance
“…All nine in-game learning analytics discussed above are expected to provide the assessment data needed to measure student achievement as well as the achievement of predefined learning outcomes in STEM learning as learning analytics involves the use of big data and data mining to boost learning assessment (Serrano-Laguna et al, 2013). Through the use of analytic learning in serious games for STEM learning, teachers will be able to take proactive steps to assist the lower performing students can also keep students motivated (Daoudi et al, 2017). Besides, information derived from student interactions with serious games can significantly improve the evaluation of games and allow both teachers and institutions to make evidence-based decisions and increase their attractiveness and confidence in the use of serious games in formal education (Alonso-Fernández et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All nine in-game learning analytics discussed above are expected to provide the assessment data needed to measure student achievement as well as the achievement of predefined learning outcomes in STEM learning as learning analytics involves the use of big data and data mining to boost learning assessment (Serrano-Laguna et al, 2013). Through the use of analytic learning in serious games for STEM learning, teachers will be able to take proactive steps to assist the lower performing students can also keep students motivated (Daoudi et al, 2017). Besides, information derived from student interactions with serious games can significantly improve the evaluation of games and allow both teachers and institutions to make evidence-based decisions and increase their attractiveness and confidence in the use of serious games in formal education (Alonso-Fernández et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Towards the end of the session, players will also be able to improve their skills and performance as well as acquire particular information and knowledge. Study by Daoudi et al (2017) found that learners' assessment and measurement in serious games are extremely important for improving learning outcomes and maintaining their motivation. Besides that, learners' assessment and measurement are also relevant for exploiting to provide a solution that fits the profile and objectives or learning needs of the students.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, Bellotti et al [45] advocate that the evaluation of students' performance should consider the different learning styles and provides appropriate feedback throughout the game. Daoudi et al [46] summarize the evaluation techniques that can be used for learners' assessment, namely the use of interviews, questionnaires, scoring, and multi-agent systems. Within these, the adoption of surveys and questionnaires stands out due to its simplicity and independence from the type of game adopted.…”
Section: Introductionmentioning
confidence: 99%
“…A avaliação pode ser definida como o processo de julgamento do desempenho do aluno (para reforçar, orientar e corrigir suas competências) ou eficácia do JS (para melhorá-lo, e.g., em aspectos de usabilidade) (Daoudi et al, 2017). A avaliação pode ser: (1) da reação ("os alunos gostaram do jogo?…”
Section: Introductionunclassified
“…A avaliação da aprendizagem define o grau de assimilação do conteúdo, transmitido pelo objeto de aprendizagem, i. e., verifica o alcance dos objetivos instrucionais (conhecimentos, habilidades e atitudes) (Kirkpatrick e Kirkpatrick, 2016). A avaliação do desempenho é definida como o processo de coleta, revisão e uso de dados, para fornecer feedback ao aluno sobre seus erros e acertos e melhorar seu desempenho atual (Bellotti et al, 2013;Daoudi et al, 2017). O feedback é a informação fornecida por um agente sobre aspectos de desempenho ou compreensão e avaliação complementar (Hattie e Timperley, 2007).…”
Section: Introductionunclassified